BLANCHOT IN THE NRF, 1960–63: an approach to the infinite conversation. Issue 5 (3rd September 2021) - Hewson, Mark
Abstract: In essays written between 1960 and 1963, Blanchot embarks on a new line of thought, beginning with fundamental philosophical division between language and vision. The contrast between the two domains is possible to the extent that they constitute two distinct modes of manifestation, each with its own space and its own conditions. The implications of this division emerge more clearly if one follows its elaboration through the column that Blanchot wrote for the La nouvelle revue française ( NRF ) during these years. Working through the essays in the sequence and the context of their original production, one can recognize how the thesis of a discontinuity in the relation to the world, given only in language, and not in perception, is formulated as a response to the intellectual and social environment of his time.